2013
DOI: 10.3109/15569527.2013.834496
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress status in patients with melasma

Abstract: The results show that the balance between oxidant and anti-oxidants was disrupted and the oxidative stress increased in melasma. These results improve the understanding of etiology-pathogenesis of the disease and its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 34 publications
4
64
2
2
Order By: Relevance
“…[28] In this study there is no significant correlation between MDA levels with severity of melasma (p> 0.05), but there is a tendency of increasing severity of melasma in higher levels of MDA. (Table 6) This is consistent with the results of research by Seckin et al (2013) that failed to show a significant relationship between levels of serum MDA with MASI values (p> 0.05). [12] Oxidative stress is an imbalance between prooxidant state with antioxidant, because ROS formation exceeds the ability of the antioxidant defense system, or decrease, or the constant state of antioxidant capability.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…[28] In this study there is no significant correlation between MDA levels with severity of melasma (p> 0.05), but there is a tendency of increasing severity of melasma in higher levels of MDA. (Table 6) This is consistent with the results of research by Seckin et al (2013) that failed to show a significant relationship between levels of serum MDA with MASI values (p> 0.05). [12] Oxidative stress is an imbalance between prooxidant state with antioxidant, because ROS formation exceeds the ability of the antioxidant defense system, or decrease, or the constant state of antioxidant capability.…”
Section: Discussionsupporting
confidence: 82%
“…[26] MDA is an end product of lipid peroxidation membrane and is one of a biomarker of oxidative stress. [12] In Table 5 is also evident that the group of Melasma, found a significant positive correlation between the duration score of exposure to sunlight with MDA levels (p <0.001), where the higher the score, the higher the duration of exposure to MDA. Coefficient correlation between the two variables is strong (R = 0.669), while in the control group, there were no significant correlation between the duration score of exposure to MDA levels (p> 0.05) but there is a tendency of increasing the duration of sun exposure, MDA has increased as well.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…While a genetic component is probably involved in melasma, sun exposure and hormonal changes/ imbalance are exacerbating factors but not causative ones. As there were no studies evaluating the role of oxidative stress in melasma, it was recently reported for the first time that the balance between oxidants and antioxidants was disrupted and oxidative stress was increased in melasma [43]. Prior to this finding, various antioxidants had been reported in the past as improving melasma.…”
Section: Melasmamentioning
confidence: 91%